Measures for the Core Outcome Set for Research Evaluating Interventions to Prevent and/or Treat Delirium in Critically Ill Adults: An International Consensus Study (Del-COrS). (3rd April 2023) - Rose, Louise; Blackwood, Bronagh; Needham, Dale M.; Devlin, John W.; Clarke, Mike; Burry, Lisa D.; ,
Abstract : OBJECTIVES: To gain consensus on measurement methods for outcomes (delirium occurrence, severity, time to resolution, mortality, health-related quality of life [HrQoL], emotional distress including anxiety, depression, acute stress, and post-traumatic stress disorder, and cognition) of our Core Outcome Set (COS) for trials of interventions to prevent and/or treat delirium in critically ill adults. DESIGN: International consensus process. SETTING: Three virtual meetings (April 2021). PATIENTS/SUBJECTS: Critical illness survivors/family, clinicians, and researchers from six Countries. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Measures (selected based on instrument validity, existing recommendations, and feasibility) and measurement time horizons were discussed. Participants voted on instruments and measurement timing (a priori consensus threshold ≥ 70%). Eighteen stakeholders (28% ICU survivors/family members) participated. We achieved consensus on the Confusion Assessment Method-ICU or Intensive Care Delirium Screening Checklist to measure delirium occurrence and delirium resolution (100%), Hospital Anxiety and Depression Scale for emotional distress (71%), and Montreal Cognitive Assessment-Blind for cognition (83%). We did not achieve consensus on EQ-5D five-level for HrQoL (69%) or its measurement at 6 months. We also did not achieve consensus on the Impact of Event Scale (IES)–Revised or IES-6 for post-traumatic stress (65%) or on measurement instruments for delirium severity incorporating delirium-related emotional distress. We were unable to gain consensus on when to commence and when to discontinue assessing for delirium occurrence and time to resolution, when to determine mortality. We gained consensus that emotional distress and cognition should be measured up to 12 months from hospital discharge. CONCLUSIONS: Consensus was reached on measurement instruments for four of seven outcomes in the COS for delirium prevention or treatment trials for critically ill adults. Further work is required to validate instruments for delirium severity that include delirium-related emotional distress.